STUDY ON THE ABILITY OF STUDENTS IN WRITING NARRATIVE ESSAY - System, Administrator; Vony Purnama, I Gusti Agung (Sphota : Jurnal Linguistik dan Sastra, 2018)
This study aims to find out the ability of the students in writing a narrative essay and to find out their difficulties in writing it. The students under concern were the second-semester students of academic year 2016 taking the English 2 subject at STIKOM Bali Dual-Degree Program. This study used the theory of Writing particularly Narrative Writing, and theory of English Grammar. The theory of Writing was used to measure the studentsâ ability in making a narrative writing. The theory of English Grammar was used to measure their ability in using the grammar. The result of this study showed that the highest score and also the lowest score of the studentsâ narrative writing were in the part of idea of the content. The proficient category was in the part of vocabulary and mechanic, but some of them also need to improve their vocabulary or the varied wording. There were some difficulties faced by the students in writing narrative essay. The first one was in focusing to the idea of the writing, the use of the varied words, and the use of the correct grammar. Then it can be concluded that they need to improve their focus on the idea and in terms of the details, words, and the most important one is in using the correct grammar.    Keywords: narrative writing, ability, difficulty